Sampling and analyses of polychlorinated dibenzo dioxins (PCDDs) and polychlorinated dibenzo furans (PCDFs) emissions in South Africa: A practitioner’s guide - Posthumus, D.L.; Woollatt, G.B. (Clean Air Journal, 2016)
Dioxins and furans are toxic chemicals. A draft report released for public comment in September 1994 by the US Environmental Protection Agency clearly describes dioxin as a serious public health threat. The public health impact of dioxins may rival the impact that dichlorodiphenyltrichloroethane (DDT) had on public health in the 1960’s. According to the United States Environmental Protection Agency(USEPA) report, not only does there appear to be no “safe” level of exposure to dioxin, but levels of dioxin and dioxin-like chemicals have been found in the general US population that are “at or near levels associated with adverse health effects.” With this in mind the purpose of this paper is to provide an overview of the current dioxin and furan emissions from industry in South Africa, in terms of compliance with the relevant emission limit values (ELVs) and the current challenges faced with the monitoring and analysis thereof.